How Should Translators Go About Their Roles in the Modern World? - Abdulmajeed Al-Ogaili, Assist. Prof. Dr. Abdulsalam (Basra studies journal, 2025)
When one considers the roles of translators, a simplistic answer might be that they convert text from a source language to a target language. However, the reality is far more complex. He/she will be surprised to discover that there is much more to it than that. In recent times, the meanings and tools of communication have changed mainly, and translators have moved in a new way, adjusting their professional aims and vision to mirror the next age of a new international society Technology makes everyday cross-cultural communication commonplace today. Consequently, translators no longer think of themselves as lonely persons, but as international ambassadors who serve an increasing number of communities. This study stems from the fact that translation requires highly qualified translators who may act as mediators, editors, readers, writers, localization experts, etc., to serve today’s communications. The results showed an increasing importance of the multi-faceted nature of the translators’ role so that the reader or the listener cannot feel the difference between the original and the translation, but rather read or heard it the same as the original .